Peranan Sistem Informasi Akuntansi Penjualan Kredit Dalam Meningkatkan Efektivitas Pengendalian Intern Piutang Dan Penerimaan kas : Studi Kasus pada PT Trinunggal Komara - Hastoni, Hastoni; Aprilisabeth, Dewi Susanti (Jurnal Ilmiah Ranggagading (JIR), 2008)
The goal of this research is to evaluate how far the application of credit selling accounting system is able to increase internal control effectiveness of credit and cash revenues. The evaluation has pupose to find out if selling procedure, internal control of credit, and cash revenues carried out by the company has been in accordance with the procedure, so that it can be accounted for. The result of this research shows that PT Trinunggal Komara has carried out the procedure properly in accounting information system, either credit selling procedure, internal control of credit, or cash revenues. Nevertheless, the evaluation result shows that there are some weaknesses need to be improved, so that the procedure implementation in accounting information system will take place as expected. Based on hypothesis test result, to be found out that point z-count equals 3,48. Whereas, on normal distribution table, it can be known that point z-table equals 0,9998. Point z-count (3,48) z-table (0,9998), Ho is rejected and Ha is accepted. It can be concluded that information system of credit selling accounting has significant role toward control effectiveness of internal credit and cash revenues at PT Trinunggal Komara. Determinant coefficient in the amount of 48,43% indicates that 48,43% for control effectiveness of internal credit and cash revenues can be determined by accounting information system of credit selling and the rest (51,57%) is influenced by other factors out of internal control of credit and cash revenues. Keywords: Accounting information system; Credit selling; Internal control.